The Role of Knowledge Management in Raising the Saudi Universities Performance Efficiency: An Applied Study on the Administrative Body of King Abdulaziz University - Alsharyofi, Maher Saif (International Journal of Informatics and Information Systems, 2022)
This study aimed at identifying the role of knowledge management in raising the efficiency of the performance of the administrative body at King Abdulaziz University. In light of this goal, a number of hypotheses were developed and tested by preparing a questionnaire comprising two variables, namely knowledge management (information technology, organizational culture, organizational structure) and the performance of the administrative body (personal elements, performance elements, knowledge of job requirements). This study was conducted at King Abdulaziz University. The necessary information was obtained through the questionnaire tool prepared for this purpose. Data were collected from 304 individuals of the administrative body of King Abdulaziz University. The results were analyzed using correlation and regression analyzes of the SPSS program. The snowball sample method was relied upon, and the link was sent to a number of the administrative body with a recommendation for them to distribute it among their university colleagues. In light of this, 315 responses were obtained, 11 responses were excluded because they were not valid. Consequently, the responses valid for analysis were 304 questionnaires. Then the student concluded with a set of recommendations related to the research variables.